The impact of political action on labour movement strength : trade union revitalisation in Africa - Oyelere, Michael A.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
In light of the decline of trade union membership and the role TU are expected to play in industrial relations, this book explores the consequences of government action and the economic policies on TU membership, investigating the forms of political action undertaken by TU and reviewing the conditions under which these actions succeed or fail.
Keywords: Labor unions -- Africa; Labor unions -- Nigeria; Labor unions -- Political activity -- Africa; Labor policy -- Africa